The effects of maternal dietary supplementation of cholecalciferol (vitamin D₃) in conjunction with 25(OH)D₃ on sow and pig performance - Thayer, Morgan Taylor (Kansas State University, 2018)
A thorough literature review on feeding vitamin D₃ and 25(OH)D₃ revealed a large amount of research conducted in swine and poultry. In general, increasing vitamin D₃ concentrations or adding 25(OH)D₃ to the maternal diet increases the vitamin D₃ status of the dam and often the progeny as well. Varying results have been reported on the practical and valuable impacts of this elevated status with some topics including improved sow performance, changes in muscle fiber morphometrics, and growth performance to market. The first experiment used a total of 69 sows and the progeny from one group of 22 sows to determine the effects of feeding a combination of vitamin D₃ and 25(OH)D₃ to the sow. Differences in sow productivity and growth performance of progeny due to dietary treatment were not observed (P > 0.05). When pigs were sacrificed at birth, there were no treatment effects for all fiber morphometric measures (P > 0.170), except primary fiber number and the ratio of secondary to primary muscle fibers (P < 0.014). Pigs from the CON and DL fed sows had less primary fibers than pigs from sows fed the DH treatment (P < 0.046), but did not differ from each other (P = 0.732). These results suggest progeny went through a longer prenatal period of primary myogenesis which delayed the onset of secondary myogenesis. Pigs from DL fed sows had a smaller secondary to primary muscle fiber ratio compared to pigs from sows fed the CON treatment (P = 0.016), with pigs from sows fed DL treatment not differing from either (P > 0.057). There were treatment x time interactions for all sow and pig serum metabolites (P < 0.001). Therefore, we chose to compare treatment means within time period. At all time periods, sow serum 25(OH)D₃ concentrations differed for all treatments with the magnitude of difference largest at weaning (P < 0.011). The second and third experiment investigated the impact of adding benzoic acid and an essential oil blend to diets and creep feed. When these additives were included in growing pig diets in a 28-d trial, a main effect of time (P < 0.001) was detected where there was no evidence of difference during the first 3 weeks for ADG and G:F, however both responses decreased during the final week of the experiment (P < 0.001) and average pen BW increased (P < 0.001) for all time points. There was a treatment x time interaction (P = 0.003) for ADFI where during the first 3 weeks, there was no evidence of difference due to dietary treatment, but during the final week of the study, pigs consumed more (P = 0.007) of the control diet (2.38 kg/d control vs. 2.24 kg/d benzoic acid paired and essential oil blend). Fecal samples collected provided no evidence of differences (P > 0.05) in fecal pathogens due to dietary treatment. When these additives were included in the maternal diet and in the creep feed, they did not (P > 0.05) affect sow performance or preweaned piglet performance. Fecal swabbing of pigs the day before weaning showed they did not eat the creep feed and, therefore, no (P > 0.05) improvements in growth performance were observed in the nursery. In conclusion, adding benzoic acid and an essential oil blend to diets and creep feed did not affect growth performance and combining vitamin D₃ and 25(OH)D₃ in the maternal diet improved the vitamin D₃ status of the dam and progeny and increased primary muscle fibers at birth.
Keywords: Vitamin D₃; Calcidiol; Muscle fibers; Swine; Essential oils; Benzoic acid